2005
DOI: 10.1038/sj.onc.1208802
|View full text |Cite
|
Sign up to set email alerts
|

PKB/Akt induces transcription of enzymes involved in cholesterol and fatty acid biosynthesis via activation of SREBP

Abstract: Protein kinase B (PKB/Akt) has been shown to play a role in protection from apoptosis, cell proliferation and cell growth. It is also involved in mediating the effects of insulin, such as lipogenesis, glucose uptake and conversion of glucose into fatty acids and cholesterol. Sterolregulatory element binding proteins (SREBPs) are the major transcription factors that regulate genes involved in fatty acid and cholesterol synthesis. It has been postulated that constitutive activation of the phosphatidylinositol 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
312
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(334 citation statements)
references
References 76 publications
19
312
2
1
Order By: Relevance
“…Lithium did not significantly inhibit ethanol-induced accumulation of TG and ceramide. While activation of AMPK inhibits lipogenesis in peripheral tissues [36], activation of Akt enhances lipogenesis [37]. Further studies on the activities and subcellular localization of AMPK and Akt may give insight into the roles of these protein kinases particularly during neurodegeneration of the developing brain by ethanol and the neuroprotective action of lithium.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium did not significantly inhibit ethanol-induced accumulation of TG and ceramide. While activation of AMPK inhibits lipogenesis in peripheral tissues [36], activation of Akt enhances lipogenesis [37]. Further studies on the activities and subcellular localization of AMPK and Akt may give insight into the roles of these protein kinases particularly during neurodegeneration of the developing brain by ethanol and the neuroprotective action of lithium.…”
Section: Discussionmentioning
confidence: 99%
“…However, mammary-specific over-expression of a constituently active Akt1 more than doubled the milk fat concentration (Schwertfeger et al, Milk fat depression 2003). Activation of Akt1 increases lipid synthesis through modification of multiple levels of SREBP1 regulation (Porstmann et al, 2005). First, Akt1 promotes processing of SREBP1, increasing nSREBP1 synthesis (Porstmann et al, 2005;Du et al, 2006).…”
Section: Sterol Response Element-binding Protein-1mentioning
confidence: 99%
“…Activation of Akt1 increases lipid synthesis through modification of multiple levels of SREBP1 regulation (Porstmann et al, 2005). First, Akt1 promotes processing of SREBP1, increasing nSREBP1 synthesis (Porstmann et al, 2005;Du et al, 2006). Secondly, nSREBP1 is targeted to proteosomal degradation by GSK3b-dependent phosphorylation, and Akt1 may increase nSREBP1 abundance by inactivating GSK3b (Rudolph et al, 2007;Jump et al, 2008).…”
Section: Sterol Response Element-binding Protein-1mentioning
confidence: 99%
“…1A shows a simplified representation of the kinase cascades activated by insulin in mammalian liver, highlighting the pathways that are felt to activate transcription of SREBP-1c (lipogenesis) or inhibit transcription of PEPCK (gluconeogenesis). Previous reports suggest that insulin-mediated stimulation of SREBP-1c expression is dependent on PI3K (15)(16)(17)20). The downstream pathway by which PI3K regulates SREBP-1c transcription in liver remains unclear.…”
mentioning
confidence: 98%
“…1A). Inhibitor studies in cultured cells, and gene knockout experiments in mice, have shown that this pathway is required both for inhibition of FoxO1 activity (13,14) and for induction of SREBP-1c expression (15)(16)(17). Therefore, it is likely that the bifurcation must occur distal to Akt.…”
mentioning
confidence: 99%